Molecular mapping of a novel locus S68 for intrasubspecific hybrid sterility in indica-indica hybrid - XuanChen Song; Ying Yang; QiuHong Pu; JiaWu Zhou; YongGang Lv; Xiaohan Jiang; Jing Li; XianNeng Deng; DaYun Tao; Yu Zhang (Scientific Reports)
Abstract Oryza. sativa subsp. indica, a subspecies of Asian cultivated rice, plays a crucial role in global rice production, particularly in the utilization of hybrid vigor. However, the genetic basis of hybrid sterility among indica-indica intrasubspecific hybrids remains elusive, hindering the effective exploitation of heterosis in rice breeding programs. In this study, a near isogenic line (NIL) was developed using the indica variety Swarna as the donor parent and the indica variety IR64 as the recurrent parent. A novel locus, designated S68, responsible for intrasubspecific hybrid sterility was mapped to the region between RM14247 and RM3413 on the short arm of chromosome 3, spanning approximately 190 kb. S68 followed one-locus allelic interaction model. In IR64/NIL-S68 hybrids, the gametes from IR64 exhibit a transmission advantage, while those from Swarna are aborted in the heterozygote. This is the first hybrid sterile locus identified in indica-indica intrasubspecific hybrids, which enhances our understanding of the genetic mechanisms underlying intrasubspecific hybrid sterility and the genetic divergence within indica rice, thereby providing guidance for hybrid breeding programs within the indica subspecies.